Cooperative National Project of Digitisation of Archival, Library and Museum Holdings “ Croatian Cultural Heritage&#8221 - Ivanović, Jozo (Array, 2007)
The cooperative national project of digitisation of archival, library and museum holdings “ Croatian cultural heritage” is geared at promoting and assisting the systematic and standardized approach to the digitisation of material in cultural institutions, forming and offering cultural content and services by way of digital copies and use of information technologies in the protection, processing and use of materials. The development of comprehensive widely accessible content in digital form is one of the key assumptions for the protection and evaluation of cultural heritage, for networking and presentation of Croatian cultural heritage in European, regional and other cultural networks, for the preservation of cultural diversity and use of cultural contents in education, tourism and other service industries. The project is aimed at formulating the long-term policy of digitisation and promotion of institutional, technological, professional and organisational capacities and infrastructure considered necessary for developing comprehensive, usable and sustainable cultural contents and services in a digital environment.